The Impact of Urban Growth on Market activities in Gombe Metropolis - Gaya, Ibrahim Faruk; Audu Zanuwa, Mu’azu; Adamu Muhammad , Kamaludeen; Ahmed Usman, Mashkurah; Muhammad , Shehu (Research Centre of Inorganic Materials and Complexs, 2020)
ABSTRACT Urban growth concept has dragged the attention of several scholars of different fields of study for decades. Urban growth refers to expansion of urban centres in size due population growth, which hiked the number of buildings in urban centres around the world. The finding of the paper indicate that Gombe Metropolis expanded by (85 hectares) each year from 2000 to 2010 and the expansion of Gombe Metropolis occur in all direction. The rate at which Gombe Metropolis expand grown to (203 hectares) each year from 2010 up to date. Therefore, the rate at which Gombe metropolis expanded increases by 138% from 2010 to date and how number of markets increases to 16 currently from 12 in the year 2010. This paper study the Impact of urban growth on market in Gombe Metropolis. Coordinate of markets of existing markets was collected. For second set of data used in this paper i.e. secondary data which include map of Gombe metropolis, related journals, text books, published and unpublished document, and Newspaper were consulted. The data generated from questionnaire administration were analysed using tables, graphs and charts. Satellite images showing how urban growth is taken place in Gombe Metropolis were also analysed. The study examines the impact of urban growth on Gombe Metropolis markets activities over the period of study. The findings of the study indicate emergence of new markets in the study area over the years of study as a result of urban expansion that occur in Gombe Metropolis. It also indicated that the new established markets were located in areas where urban growth take place in study area and these new markets are patronized by people within the environment or vicinity of the markets. Most of the newly emerged markets are located at the periphery of the town where urban expansions occur rapidly.